PENINGKATAN KEMATANGAN PILIHAN KARIR PESERTA DIDIK MELALUI LAYANAN INFORMASI BERMUATAN INTERNET - Revlina, Intan; Lestari, Indah; Sumarwiyah, Sumarwiyah (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The purpose of this study are: 1) to describe the implementation of Internet-based information services in an effort to increase the consolidation of students' career choices. 2) Obtaining Increased Consolidation of Student Career Choices through Internet-Based Information Services. The results of research on Strengthening Career Choices Students in the Pre-Cycle obtained a score of 14 (47%) in the Poor category, in Cycle I obtained an average score of 20 (67%) in the Enough category and in Cycle II obtained an average score of 2 (87%) in the Very Good category. The conclusions of this study are: "1. Internet-Based Information Services can Increase the Consolidation of Student Career Choices. 2. Consolidating Student Career Choices can be increased through Internet-Based Information Services, Consolidation of Student Career Choices in Cycle I obtained a score of 77 (76%) in the Enough category. Cycle II obtained a score of 91 (79%) in the Good category.